John H. Cherry, Digest of the Laws and Ordinances of the City of Little Rock 168, § 399 (1882) - (:unkn) unknown (My University, 1871)
Prohibited carrying of a pistol, revolver, Bowie knife, dirk, rifle, shot gun, slungshot, colt, or metal knuckles while engaged in a breach of the peace. Punishable by a fine of $25-500.
Keywords: CARRY - INTENT TO COMMIT CRIME